“Istrian exodus”: Between official and alternative memories, between conflict and reconciliation - Virloget, Katja (Ethnologies)

(untitled) (Association Canadienne d’Ethnologie et de Folklore, 2017)
This article touches on the sensitive topic of the so-called Istrian exodus, which has been stirring conflict in political discourses between Italy and the former Yugoslavia, later Slovenia and Croatia, for more than six decades. It analyses different forms of case-studies of peace-making memories, such as political discourses, commemorations, monuments, literature, film, theatre, etc. The research focuses on the emptied and resettled space of Istria after the exodus. The author takes into consideration literary and fine art works or performances that have touched upon that contested past, provided reflections, or had some impact on the present-day Istrian population. It analyses the relation between institutional and alternative forms of memory, and the interplay between conflicting and appeasing discourses.